2018
DOI: 10.1371/journal.pmed.1002714
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and treatment moderators of internet interventions for adult problem drinking: An individual patient data meta-analysis of 19 randomised controlled trials

Abstract: BackgroundFace-to-face brief interventions for problem drinking are effective, but they have found limited implementation in routine care and the community. Internet-based interventions could overcome this treatment gap. We investigated effectiveness and moderators of treatment outcomes in internet-based interventions for adult problem drinking (iAIs).Methods and findingsSystematic searches were performed in medical and psychological databases to 31 December 2016. A one-stage individual patient data meta-analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
211
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 209 publications
(245 citation statements)
references
References 65 publications
28
211
1
5
Order By: Relevance
“…Recent evidence from a meta‐analysis of individual patient data evaluating the effectiveness and moderators of internet interventions for adult drinkers suggested that future research should identify for whom the interventions work best, the most favourable context and how the interventions work . Such conclusions are similar to those in the present study and from process studies of brief interventions , which emphasize the need for more studies on the mechanisms of behaviour change, including for personalized feedback and technology‐based interventions .…”
Section: Discussionsupporting
confidence: 82%
“…Recent evidence from a meta‐analysis of individual patient data evaluating the effectiveness and moderators of internet interventions for adult drinkers suggested that future research should identify for whom the interventions work best, the most favourable context and how the interventions work . Such conclusions are similar to those in the present study and from process studies of brief interventions , which emphasize the need for more studies on the mechanisms of behaviour change, including for personalized feedback and technology‐based interventions .…”
Section: Discussionsupporting
confidence: 82%
“…Age moderated the effect on depression, and the subgroups with older participants showed significantly higher effects for stress, depression, and burnout. The enhancing role of older participants was previously shown (77) and could be explained by the higher self-disciplined engagement of participants that is required by most self-help interventions. However, this finding should be interpreted with caution, as RCT in younger participants in an occupational context are rare.…”
Section: Discussionmentioning
confidence: 89%
“…The literature on guided ICBT for alcohol misuse, however, is still sparse. A recent individual patient data meta-analysis found guided internet interventions for alcohol misuse to be superior to unguided ones [23]. However, the analysis did not distinguish between ICBT and other kinds of internet interventions, such as brief interventions.…”
Section: Guidance In Icbt For Alcohol Misusementioning
confidence: 95%